9.5k views
0 votes
Can you solve for ¨h¨

a = ch + f

If you can answer today, that would be great! Thanks

User Jwqq
by
5.3k points

2 Answers

5 votes

Answer


\boxed {h= (a-f)/(c)}



\boxed {a = ch+f} \rightarrow \boxed {a - f = ch}\rightarrow \boxed {(a-f)/(c) = h} \rightarrow \boxed {h= (a-f)/(c)}


Detailed Explanation

In this problem, we are solving for h.


Let's start.



a = ch+f



a - f = ch



(a-f)/(c) = h


Therefore, the answer would be
\boxed {h= (a-f)/(c)}




Can you solve for ¨h¨ a = ch + f If you can answer today, that would be great! Thanks-example-1
User Dhananjay Kyada
by
5.3k points
5 votes

Subtract f from both sides:



a - f = ch


Divide both sides by c to get h by itself and get your answer:



\boxed{(a-f)/(c) = h}

User Alexander Otavka
by
5.2k points